STRUKTUR KOMUNITAS MANGROVE DAN TEKANAN YANG DIHADAPI AKIBAT AKTIVITAS MASYARAKAT: STUDI KASUS PESISIR PANTAI SEBANJAR, KABUPATEN ALOR - Sari Hauliah Ahmad Koda (OSEANA, 2021)
This study aims to analyze ecologically the mangroves in Sebanjar coastin Alor Regency by looking at the important value index and diversity index, as well as to see and describe the behaviors of coastal communities that have positive and negative impacts on the mangrove ecosystem. The method used to determine the ecological condition of mangroves is the quadratic transect method to obtain data on density, frequency, dominance, important value index and mangrove diversity index. The method of interview and observation at the research site was conducted to determine the people behavior that had positive or negative impacts on the mangrove ecosystem. The result shows that there were three species of mangrove in this location, i.e. Sonnetaria alba, Bruguiera sexangular, and Lumnitzera racemose. The average Diversity Index in each location indicated that the ecological condition of the mangrove forest is in a depressed condition due to human activities. The behavior of the community that has a negative impact on the mangrove forest on the coast of Sebanjar Beach is illegal logging, garbage disposal in the coastal area, deflection of fresh water for irrigation and the conversion of mangrove forest land into fields and salt ponds. However, there are community behaviors that have a positive impact on mangrove forests, namely by participating in planting and maintaining mangroves that have been provided by the government and non-govermental organization.